[PP.07.06] URINARY PROTEOME ANALYSIS IDENTIFIED NEPRILYSIN AND VCAM AS KEY PROTEINS IN THE DEVELOPMENT OF DIABETIC NEPHROPATHY. (September 2016) - Bardaji, B.; Guillen-Gomez, E.; Ferrer, S.; Brotons, C.; Knepper, M.A.; Carrascal, M.; Abian, J.; Mas, J.M.; Calero, F.; Ballarin, J.A.; Fernández-Llama, P.
Abstract : Objective: Diabetic nephropathy (DN) is the major cause of end-stage renal disease. Renin-angiotensin system (RAS) inhibition is the preferred treatment to slow its progression. We have studied the urinary proteomes of patients with DN (high albuminuria) to investigate the pathophysiology of renal disease and identify disease markers and predictors of clinical outcome. Design and method: We included diabetic men with (n = 9) and without DN (n = 12) (control cohort). Data collection included clinical and laboratory evaluation of blood and urine at baseline (control cohort and DN-basal), and in patients with DN after 3 months of losartan treatment (DN-treated). Urinary proteome was analyzed and quantified by Tandem Mass Tag (TMT) labeling on a LTQ-Orbitrap mass spectrometer. Results: Patients enrolled in the study showed no differences regarding basic clinical parameters. Urinary proteome analysis have identified 166 differentially excreted proteins when comparing the proteomes of controls and DN patients, 27 comparing DN-treated and DN-basal patients, and 182 among patients DN-treated and controls. Systems biology approach comprising functional proteomic networks and artificial neural networks (TPMS technology) have identified 80 key proteins involved in the pathophysiology of DN and 15 key proteins involved in the efficacy of losartan. There are 7 proteins identified in the urine proteome that are essential in both DN pathophysiology and treatment efficacy. Vascular cell adhesion molecule-1 (VCAM-1) and the angiotensin-metabolizing neutral endopeptidase neprilysin (NEP) stand out from the other identified proteins because they are the only ones that are DN effectors. They are differentially expressed in the urinary proteome and are also key proteins in both DN pathophysiology and RAS inhibition efficacy. Conclusions: NEP is a membrane-bound zinc-containing metalloproteinase showing great abundance in the brush border of proximal renal tubular cells. NEP is responsible for the processing and catabolism of several vasoactive peptides including angiotensin II and endothelin which may explain its pathogenic role in the development of DN.